Why Zakat Collection in Indonesia is Not As Effective As it is in Malaysia - Purwatiningsih, Aris Puji; Yahya, Muchlis (LP2M IAIN kUDUS, 2020)
The purpose of this article is to find out the practices and problems of why zakat in Indonesia have not been manage optimally as it is in Malaysia. This study applies descriptive method by collecting data and information from previous articles about zakat, especially zakat management in Indonesia and Malaysia. The findings show that the main problems in managing zakat in Indonesia are: first, there is no government regulation that requires all Muslim citizens who have property that reach nisab requirement to give out zakat. Secondly, Moslem community prefers to pay zakat to the people whom they have already known rather than to the existing formal zakat institutions. Third, there is a lack of good cooperation between zakat institutions owned by the government and the other institutions run by private parties. The result of this of this study may be useful to be used by all parties involved in zakat management so that it can be managed more optimal.